Relationship Betweenparticipant’s Learning Readiness Educate Through Onlinewith the Learning Results on English Courses - Mahda Safitri; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is based on the low learning outcomes of students online in English courses at the English Tutorial Center Padang, it is suspected that there is something to do with students' readiness to learn. The purpose of this study is to reveal: (1) a description of students' readiness to learn online, (2) student learning outcomes in English courses at the English Tutorial Center Padang, and (3) reveal the relationship between students' readiness to learn online and learning outcomes in the English course at the English Tutorial Center Padang. This type of research is descriptive correlational research through a quantitative approach. The population of this research is English course students for the period of July - August 2020, totaling 35 people and a sample of 70%, namely 24 people with cluster random sampling technique. The data collection technique used is a questionnaire and the tool used is a questionnaire. The data analysis technique used the percentage formula and the spearman rho formula.The results of this study indicate that: 1) students' online learning readiness in English courses at the English Tutorial Center Padang is low; 2) student learning outcomes in English courses at the English Tutorial Center Padang are low; 3) there is a significant relationship between students' readiness to learn online and their learning outcomes in English courses at the English Tutorial Center Padang. The suggestion of this research is that the manager of the English course at the English Tutorial Center Padang should provide facilities that will be used  during  learning  so  that  it  can  foster  enthusiasm  and  readiness  to  learn  students. Instructors should be creative when using learning media so that they can bring up the enthusiasm and readiness of students to learn in the implementation of learning activities.Keywords: Learning Readiness,Learning Outcomes